OPTIMIZATION OF QUALITY AND PRODUCTIVITY OF DAILY GOAT BUSINESS GROUP IN BLIMBING VILLAGE, REJOTANGAN DISTRICT, TULUNGAGUNG REGENCY THROUGH TECHNOLOGICAL INNOVATION - Nove Hidajati; M. Gandul Atik Yuliani; Ratna Damayanti (Jurnal Layanan Masyarakat (Journal of Public Services), 2022)
"Karya Putra Mandiri" Livestock Farmer Group and "Makmur Sentosa" Livestock Group, Kec. Rejotangan Kab. Tulungagung is a foster partner of the Unair FKH Community Service Team. A common problem for breeders and administrators of the "Karya Putra Mandiri" Livestock Farmer Group and "Makmur Sentosa" Livestock Group, Kec. Rejotangan Kab. Tulungagung is a problem in production, among others are reproductive disorders, low pregnancy rates, low productivity in their dairy goats. The solution offered is to increase the skills and knowledge of dairy goat farmers in the "Karya Putra Mandiri" and "Makmur Sentosa" livestock groups on how to handle reproductive cases through synchronization of lust. Another problem is the "Karya Putra Mandiri" Livestock Farmer Group and the "Makmur Sentosa" Livestock Group, Kec. Rejotangan Kab. Tulungagung is a management problem. The solution offered is to increase the knowledge and assistance of dairy goat farmers in the “Karya Putra Mandiri” and “Makmur Sentosa” livestock groups in dairy goat milk processing, packaging and product licensing. The method used in the implementation of this community service activity is by; (1) Development and training stage; (2) Monitoring and evaluation stage. To evaluate the level of knowledge and understanding of the material given, pretest and posttest are given. This Community Service program activity was carried out from March to October 2018. Extension activities and training on Laserpuncture and Sexual Synchronization Technology were carried out using the tutorial method, then continued with discussions. The implementation of this Community Service Activity requires a budget of 30 million rupiah which is planned to be used in several posts including for equipment, consumables, travel, accommodation, and others.